2015
DOI: 10.1614/ws-d-15-00037.1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the ΔG210 Protoporphyrinogen Oxidase Mutation in Illinois Waterhemp (Amaranthus tuberculatus) and an Improved Molecular Method for Detection

Abstract: Molecular assays are often implemented by weed scientists for detection of herbicide-resistant individuals; however, the utility of these assays can be limited if multiple mechanisms of evolved resistance exist. Waterhemp resistant to protoporphyrinogen oxidase (PPO)– inhibiting herbicides is conferred by a target-site mutation in PPX2L (a gene coding for PPO), resulting in the loss of a glycine at position 210 (ΔG210). This ΔG210 mutation of PPX2L is the only known mechanism responsible for PPO-inhibitor resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 18 publications
1
35
0
1
Order By: Relevance
“…This assay uses allele‐specific probes to determine whether a plant is wild type or heterozygous/homozygous for the ΔG210 mutation. The only difference between this new assay and the assay given in Wuerfell et al . is new primers that recognize both A. palmeri and A. tuberculatus PPX2 sequence, PA‐tqF1 (5′‐ TGATTATGTTATTGACCCTTTTGTTGCG) and PA‐tqR1 (5′‐ GAGGGAGTATAATTTATTTACAACCTCCAGAA).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This assay uses allele‐specific probes to determine whether a plant is wild type or heterozygous/homozygous for the ΔG210 mutation. The only difference between this new assay and the assay given in Wuerfell et al . is new primers that recognize both A. palmeri and A. tuberculatus PPX2 sequence, PA‐tqF1 (5′‐ TGATTATGTTATTGACCCTTTTGTTGCG) and PA‐tqR1 (5′‐ GAGGGAGTATAATTTATTTACAACCTCCAGAA).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This assay uses allele-specific probes to determine whether a plant is wild type or heterozygous/homozygous for the ΔG210 mutation. The only difference between this new assay and the assay given in Wuerfell et al 9 is new primers that recognize both A. palmeri and wileyonlinelibrary.com/journal/ps Figure 2. Gel image of dCAPS assays for three Amaranthus palmeri plants from population GPW.…”
Section: Ppx2 G210 Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…23 Subsequent surveys demonstrated that the ΔGly210 mutation was ubiquitous among PPO-inhibitor-resistant A. tuberculatus populations. [24][25][26] The ΔGly210 mutation confers broad cross-resistance to most PPO inhibitors. 20,21,27 The highest magnitude of resistance was reported to lactofen, with resistance:sensitive (R:S) ratios ranging from about 20 to 80, whereas resistances to most other PPO inhibitors were more modest and generally <10-fold.…”
Section: Use Of Ppo Herbicidesmentioning
confidence: 99%
“…Described in more detail in the following sections, a deletion of a glycine amino acid (termed ΔGly210) in the PPO2 enzyme confers resistance to PPO inhibitors in A. tuberculatus . Subsequent surveys demonstrated that the ΔGly210 mutation was ubiquitous among PPO‐inhibitor‐resistant A. tuberculatus populations . The ΔGly210 mutation confers broad cross‐resistance to most PPO inhibitors .…”
Section: Introductionmentioning
confidence: 99%